PENGARUH DIMENSI RELATIONSHIP MARKETING TERHADAP KEPUASAN DAN LOYALITAS NASABAH (Studi Kasus Pada BPR Argodana Pudak Payung Semarang) - Arum Istiqomawati (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2017)
The purpose of this research is to analyze and determine the effect of communication,partnership, trust, conflict complain on customer satisfaction and to analyze and determinethe effect of communication, partnership, trust, conflict complain and customer satisfaction oncustomer loyalty. The population in this study is the BPR customers Argodana Pudak UmbrellaSemarang, while the population as much as 96 respondents obtained by using purposivesampling technique. The type of data used is primary data, using the method of data collectionquestionnaire.The results of analysis by using path analysis is communication, partnership,trust, conflict complain effect on customer satisfaction. Communication, partnership, trust,complain conflict and affect customer satisfaction on customer loyalty. customer satisfaction isamong the intervening variablesinfluence of partnership on customer loyalty, however, customersatisfaction is not an intervening variable between the influence of communication, trust andconflict complaint on customer loyalty.Keywords: Communication, Partnership, Trust, Conflict Complain, Satisfaction and CustomerLoyalty